STUDY OF THE EFFECTIVENESS OF POTATO STARCH AS AN ALTERNATIVE MATERIAL IN THE PREPARATION OF COSMETICS - BENHAMID KHOULOUD; DIF SARA (Uniersité d' EL-Oued., 2025)
This study investigates the effectiveness of potato starchfrom the Solanum tuberosum Lfrom classBartina . plant collected from Oued Souf region as an alternative material in the preparation of cosmetics.we studied through In Vivo tests that include one main test.Which is represented by making a special cream to lighten the face, consisting of 10 grams of dry potato starch and about 5 ml of pure water, and applying it to the face for 20 minutes .The results of this test were not generally satisfactory due to people's lack of adherence to the method of using the cream and the short time required for this study.the physical-chemicalproperties the extract showed a significant percentage of its components such as in carbohydrates 85% andconductivity 1087 uS/cm. In antibacterial tests, we studied through In vitro tests that include four types of bacteria. The potato starch extracts showed a negative results,The Antioxidant activity, potato starch extractshowed significant antioxidant activity in the DPPH tests, where the results were very weak antioxidant activity compared to Vitamin C, with an 85% in VitCand an (less than 20% in the extract. In the anti-hemolysis test, showed minimal inhibition even at high concentrations (maximum 0.65% at 40 mg/mL). Tocopherols, in contrast, showed strong inhibition (up to 57.21% at 21 mg/mL.). In addition, the antiinflammatory activity through egg albumen denaturation test, the extract it showed an effectiveness estimate of 10%.
Applied Biochemistry
Keywords: and applying it to the face for 20 minutes .The results of this test were not generally satisfactory due to people's lack of adherence to the method of using the cream and the short time required for this study.the physical-chemicalproperties the extract showed a significant percentage of its components such as in carbohydrates 85% andconductivity 1087 uS/cm. In antibacterial tests